Affordability of Houses for Middle-Income People (MBM) in Greater Bandung Through Price to Income Ratio (PIR) Analysis - Santoso, Rahmawati (CV. Publikasi Indonesia, 2025)
Housing affordability is an important issue in the national and global development agenda, especially for middle-income people in metropolitan areas such as Greater Bandung. This study aims to evaluate the affordability of subsidized and non-subsidized housing in 2024 and project it until 2045, using a quantitative approach through Price to Income Ratio (PIR) analysis. The results showed that households with double income had a better level of affordability than households with single income. However, even dual-income households in the BMA still have difficulty reaching non-subsidized type 36 houses, and subsidized houses are not affordable for single-income households. Projections through 2045 show that the minimum wage increase is not enough to keep pace with the pace of house price increases, so affordability is likely to deteriorate. These findings indicate the need for more effective attention and policy interventions to ensure access to decent and affordable housing, particularly for MBM groups in metropolitan areas.